Relationship between acute stress response and depression among college students： the mediating role of rumination and the moderated role of perceived social support - Luo Gui; Yuan Fenghui; Mou Yunjing; Yu Haijun; Liang Jingjing; Dang Jiangbo; Gao Bin (Sichuan jingshen weisheng)
BackgroundDepression has become a public health concern that affects the physical and mental health of college students. acute stress response is a risk factor of depression. Exploring the relationship and mechanism between acute stress response and depression is of great significance for preventing and intervening depression in college students.ObjectiveTo examine the relationship between acute stress response and depression among college students， and to analyze the mediating role of rumination and the moderated effect of perceived social support， so as to provide references for the prevention and intervention of depression in college student .MethodsFrom March to April 2020， a cluster sampling method was employed to select 1 355 college students from three universities in Hubei， Jiangxi and Guangxi Zhuang Autonomous Region. Participants were assessed with Acute Stress Disorder Scale （ASDS）， Ruminative Responses Scale （RRS）， Brief form of Perceived Social Support Questionnaire （F-SozU） and Patients' Health Questionnaire Depression Scale-9 item （PHQ-9）. Pearson correlation analysis was adopted to examine the correlation between the scores of each scale. The mediating role of rumination between acute stress response and depression and the moderated role of perceived social support were examined respectively by using Model 4 and Model 14 in Macro Program Process 3.3.ResultsA total of 1 303 valid questionnaires were collected， yielding a valid response rate of 96.16%. The results of Pearson correlation analysis showed that ASDS score was positively correlated with RRS score and PHQ-9 score （r=0.649， 0.528， P<0.01） among college students. The mediation analysis results demonstrated that rumination played a partial mediating role between acute stress response and depression， with the mediating effect value of 0.273 （95% CI：0.222~0.328）， accounting for 68.59% of the total effect. Perceived social support played a moderated role in the latter path of the mediation model （rumination → depression） （β=-0.004， 95% CI： -0.017~-0.004， P<0.01）.ConclusionRumination played a partial mediating role between acute stress response and depression in college students， and perceptive social support played a moderated role between rumination and depression. ［Funded by Scientific Research Fund Project of Education Department of Yunnan Province （number， 2025J0437）］